A Comparative Analysis between Islamic Banks and Conventional Banks in Indonesia Before and After Global Financial Crisis - Lina Nugraha Rani; Eko Fajar Cahyono (Economics and Finance in Indonesia, 2018)
The objective of this study is to elaborate the comparison and examine the stability level between Islamic and conventional banks operational in Indonesia during the period of before and after Global Financial Crisis (GFC). The impact of Global Financial Crisis on Islamic and conventional banks was analyzed using the tests of IRF (Impulse Response Function) and Variance Decomposition Analysis (VDA) which existed in the VAR (Vector Autoregressive) Method. The pre (GFC) period used in this study is between January 2003 and July 2007, whereas the post GFC is between August 2007 and December 2016. The results of this study are that Conventional and Islamic Banks   are affected by macroeconomic conditions and macroeconomic turmoil in the period before and after the global financial crisis. The results of contrasting research are the responses and the effect of macroeconomic indicators on banks higher pre the GFC occurs than after the occurrence of GFC.